Road traffic injuries: psychological and social aspects - N. G. Petrova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2023)
Introduction. Despite the positive trend in recent years, the incidence of road traffic injuries and deaths from it remains high, significantly higher than in developed countries. The economic significance of the problem is determined by the high level of disability among the victims, and by the fact that a significant part of them are people of working age. The following factors contribute to the occurrence and certain outcomes of road accidents: people (behavior, health, psychological state of road users); vehicle condition; environment (road infrastructure); the state of organization of medical care for victims (including the possibility and readiness of participants and witnesses of road accidents to provide first aid). The objective was to analyze the level of driving culture and the readiness of drivers to provide first aid based on the results of self-assessment. Methods and materials. The main research method was a sociological survey, which was conducted on the basis of the Google Forms survey administration program. The survey was conducted among the population of St. Petersburg and the Leningrad region. The questionnaire developed for the study included 29 questions. All questionnaires were encrypted and processed using the Excel and Statistica 10 statistical applications. Results. Assessing their level of knowledge of the rules of the road, most of the respondents considered it as average (45.3 %) and above average (34.0 %). Only 7.5 % considered it as high. Every third (34.2 %) respondent was a participant in an road accident (including 4.9 % – road accidents with victims). 45.3 % of respondents assessed the level of driving culture as average; 39.6 % – rather low; and only 5.7 % – as rather high. The majority (83.0 %) of drivers always used seat belts. Among drivers with children, 11.8 % did not have special child restraints. 10.4 % of respondents did not have a first aid kit in their car. The readiness of drivers to provide first aid was low. Only 26.9 % of the respondents confidently answered that they could provide first aid for the victims. Conclusions. The problem of preventing road accidents and reducing mortality from them can only be solved using a systematic approach, including optimization of traffic organization, improvement of road infrastructure, condition of vehicles, improvement of the organization of medical care for victims, etc. However, the central place should be given to cultivating the culture of all road users, psychological readiness to comply with traffic rules, providing first aid.